A new tube for optimizing closed decompression and temporary intestinal splinting in ileus of the small intestine - Ermisch, J; Schneider, H (Chirurg, 1995)
Based on our experience with intestinal splinting in 52 patients, we present a new tube that we regard as having advantages over balloon tubes, thus representing a true alternative.